The ethical-legal dimension of the disruptive technology of gene editing in embryos in the framework of the social and democratic state under the rule of law - Huergo González, Inés (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2024)
Gene-editing biotechnology offers mankind the possibility of intervening in the germ line. This paper examines the aims of the intervention, the compromises and the responsibility in its application. Complementary to the ethical task is the legal task, as an expression of social values and, therefore, a theoretical review of international, EU and national regulations is necessary. Finally, the magnitude of the potential effect on humanity is examined, in its collective dimension, but without forgetting the individual dimension, i.e. the subjects directly affected by the intervention.
Keywords: gene editing; CRISPR-CAS9; health; bioethics; eugenics